Constant low-to-moderate mechanical asymmetries during 800-m track running - Girard, Olivier; Millet, Grégoire P.; Micallef, Jean-Paul (Frontiers in Sports and Active Living, 2024)
Introduction Modifications in asymmetry in response to self-paced efforts have not been thoroughly documented, particularly regarding horizontally-derived ground reaction force variables. We determined the magnitude and range of gait asymmetries during 800 m track running. Methods Eighteen physical education students completed an 800 m self-paced run on a 200 m indoor track. During the run, vertical and horizontal ground reaction forces were measured at a sampling frequency of 500 Hz using a 5 m-long force platform system, with data collected once per lap. The following mechanical variables were determined for two consecutive steps: contact time and duration of braking/push-off phases along with vertical/braking/push-off peak forces and impulses. The group mean asymmetry scores were evaluated using the “symmetry angle” (SA) formula, where scores of 0% and 100% correspond to perfect symmetry and perfect asymmetry, respectively. Results There was no influence of distance interval on SA scores for any of the nine biomechanical variables (P ≥ 0.095). The SA scores were ∼1%–2% for contact time (1.3 ± 0.5%), peak vertical forces (1.8 ± 0.9%), and vertical impulse (1.7 ± 1.0%). The SA scores were ∼3%–8% for duration of braking (3.6 ± 1.1%) and push-off (3.2 ± 1.4%) phases, peak braking (5.0 ± 2.1%) and push-off (6.9 ± 3.1%) forces as well as braking (7.6 ± 2.3%) and push-off (7.7 ± 3.3%) impulses. The running velocity progressively decreased at 300 m and 500 m compared to that at 100 m but levelled off at 700 m (P < 0.001). Discussion There were no modifications in gait asymmetries, as measured at 200-m distance intervals during 800-m track running in physical education students. The 800 m self-paced run did not impose greater mechanical constraints on one side of the body. Experimental procedures for characterizing the gait pattern during 800 m track running could be simplified by collecting leg mechanical data from only one side.